Valoración de la aportación a la resistencia en comprensión del concreto de la sílice obtenida de la cascarilla de arroz. (2022)
This research is carried out with the purpose and motivation of providing positive results about the disposal and reuse of industrial waste generated by various industries, in order to use them in various surroundings for this case engineers, this due to different negative events that have occurred in the country regarding infrastructure, so it is necessary to be objective with the career that is being studied, because, with the study of this, engineers are a social benefactor, and likewise we have a responsibility with society and the environment ambient.